1975
DOI: 10.1002/macp.1975.021760315
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the structure of the stereocomplex of poly(methyl methacrylate) in solution from NMR relaxation data

Abstract: From the values of relaxation times Tz determined on a pulse spectrometer, and from the shape of bands in high resolution (HR-) and broad line (BL-) NMR spectra, two types of protons, different in mobility, were found to exist in the associated stereocomplex of isotuctic (it-) and spdiotactic (sr-) poly(methy1 methacrylate) (PMMA). From the analysis of NMR spectra, measured at magic angle rotation (MAR-NMR), the mobility of the ester groups in the stereocomplex is shown to be greatly hindered. Temperature chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1975
1975
1994
1994

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Complex formation for isotactic (it) and syndiotactic (st) poly(methyl methacrylate) (PMMA) is most widely known among the polymeric stereocomplexes and has intensively been investigated using various techniques. [15][16][17][18][19][20][21][22][23][24][25] It has been found that when itand st-PMMA form a stereocomplex in dilute solution with a strongly complexing solvent, the solution viscosity decreases, while in a concentrated solution of complexing solvent, an increase in viscosity is observed accompanying gelation. 15 In a previous paper, we reported that a stereocomplex is formed when a ternary dilute chloroform solution of PDLA and PLLA is poured into methanol, although no change in viscosity of the dilute chloroform solution could be detected.11 Therefore, the complex seems to form not in the dilute solution but during the precipitating process.…”
Section: Introductionmentioning
confidence: 99%
“…Complex formation for isotactic (it) and syndiotactic (st) poly(methyl methacrylate) (PMMA) is most widely known among the polymeric stereocomplexes and has intensively been investigated using various techniques. [15][16][17][18][19][20][21][22][23][24][25] It has been found that when itand st-PMMA form a stereocomplex in dilute solution with a strongly complexing solvent, the solution viscosity decreases, while in a concentrated solution of complexing solvent, an increase in viscosity is observed accompanying gelation. 15 In a previous paper, we reported that a stereocomplex is formed when a ternary dilute chloroform solution of PDLA and PLLA is poured into methanol, although no change in viscosity of the dilute chloroform solution could be detected.11 Therefore, the complex seems to form not in the dilute solution but during the precipitating process.…”
Section: Introductionmentioning
confidence: 99%